Efficacy evaluation, through micro-CT, of reciprocating and rotary instruments followed by supplementary irrigant-agitation procedures in the retreatment of curved root canals - Fruchi, Lincoln de Campos (2018)
Endodontic retreatments are time-consuming and difficult to perform. Removing the root canal filling material of the original treatment with maximum efficiency and safety is a complex task that requires a good technique, patience and perseverance. This filling material is often contaminated and prevents access to areas of the canal harboring bacteria and remnants of necrotic tissue, especially in the isthmus region and in dentinal tubules. The aim of this study was to use micro-computed tomography to evaluate two protocols for the removal of root canal filling material from curved root canals of the mesial roots of mandibular molars using a reciprocating instrument followed by two different rotary instruments manufactured with different nickel-titanium alloys. The reduction in the volume of the filling material inside the root canals was evaluated. Assessments were also made of the influence of the glide path extension on root canal obturation, the extrusion of filling material after the use of the reciprocating instrument, the volume of filling material after retreatment and its presence in isthmus areas. In addition, the use of a solvent and the agitation of a 2% sodium hypochlorite solution using either passive ultrasonic irrigation (PUI) or a plastic instrument in reciprocating motion were evaluated. A total of 40 mesial roots of mandibular molars with a mean curvature of 25 degrees were selected. The teeth were radiographed digitally in the buccolingual and mesiodistal directions, with a digital Xray system (Schick CDR; Schick Technologies, Long Island, NY), using an exposure time of 0.16 s. This was done in order to select the teeth and then compose two groups with similar characteristics to ensure their anatomic homogeneity. Group homogeneity in terms of anatomy, root canal length, curvature angle, and Vertucci classification type II and IV were confirmed and showed that the study groups were well balanced. Two groups were defined according to the retreatment protocol adopted, namely RHPui (Reciproc + Hyflex + PUI) and RMEasy (Reciproc + Mtwo + EasyClean). The teeth were instrumented with the Reciproc R25 instrument and filled using the single-cone technique and AHPlus cement. Prior to the use of this instrument, canal patency was achieved by creating a glide path with PathFile instruments, throughout the entire extension of the canal in Group RHPui, and up to 1 mm short of the total canal length in Group RMEasy. In both groups, the original filling material was removed with the Reciproc R25 instrument. Xylene was used as a solvent in Group RHPui up to the middle third, but not in the apical area, in the later steps of instrumentation with Reciproc R25. In Group RHPui, the Hyflex 40.04 instrument, made with a CM nickeltitanium alloy, was used. After that, xylene solvent was applied for one minute in the pulp chamber, followed by passive ultrasonic irrigation (PUI) with 2% sodium hypochlorite using an irrisonic instrument, applied up to 2 mm short of the working length. In Group RMEasy, the Mtwo 40.04 instrument, made with a conventional nickeltitanium alloy, was used. Xylene solvent was also used in the pulp chamber for one minute, followed by application of a 2% sodium hypochlorite solution agitated mechanically with an EasyClean plastic instrument in reciprocating motion up to the full working length. The two groups were re-obturated using the warm vertical condensation technique, with a gutta-percha cone corresponding to the final instrument, and with AHPus cement. Micro-CT scans were performed after each procedure to evaluate the volume of the remaining material, the extrusion after the use of the reciprocating instruments, the final volume of the obturation at the end of the retreatment and the filling material volume in the isthmus area, both after the original obturation and after re-obturation. The results showed that the initial filling was significantly closer to the apical foramen in Group RHPui than in Group RMEasy, after the initial treatment. After performing the retreatment protocols, the complete removal of filling material from inside the root canals was not achieved in either study group, with no statistically significant difference (P > 0.05) between groups regarding this variable. In the intra-group evaluation, a statistically significant difference (P < 0.05) was found between the procedural steps regarding the reduction in filling material volume, both in the total canal length and at its different levels, except for the middle third after HyFlex, the cervical third after Mtwo, and the middle third after EasyClean. The volume of the final filling material was significantly higher (P < 0.05) than the volume of the original filling material in both study groups. The volume of filling material in the isthmus region was significantly higher after re-obturation in both groups (P < 0.05), and this increase was greater in the RMEasy Group. There was no statistically significant difference (P > 0.05) between groups regarding the total amount of time expended in the removal of filling material (P > 0.05), namely 209.40 s for the RHPui Group and 227.40 s for the RMEasy Group. There was also no statistically significant difference (P > 0.05) between groups regarding the volume of extruded filling material, namely 0.0258 mm3 (0 0.954) in the RHPui Group and 0.0037 mm3 (0 0.565) in the RMEasy Group. The Shapiro-Wilks, Mann-Whitney, Wilcoxon, Friedman and Dunn tests were used in the data analysis.